Wild Frenchmen and Frenchified Indians : material culture and race in colonial Louisiana - White, Sophie (Early American studies., 2012)
Based on a range of archival, visual, and material evidence, this book examines perceptions of Indians in French colonial Louisiana and demonstrates that material culture--especially dress--was central to the elaboration of discourses about race.